The Tribal Fanaticism (Asabiyya) Individual Behavior or Social-Political Phenomenon - Elhrabi, Ali B R; Abdul Hamid, Ahmad Faisa Faisal (Journal Al-Muqaddimah, 2017)
The idea of tribal fanaticism (Asabiyya) revolves around the sense of belonging that an individual perceives within the group with which he has a relationship with blood and descent, and sometimes alliance or neighborliness. the Arab man practiced the tribal fanaticism before Islam, both at the personal level and at the tribe level, When Islam came, the Muslim's view changed about the tribal fanaticism, the negative side of tribal fanaticism is an indecent act, the Islam has warned from it, but tribal fanaticism is sometimes a positive behavior to promote tribe affiliation. By tracing history, we find that tribal fanaticism has shifted from personal behavior in the tribe to a general orientation of this tribe, and then became a political program for access to power. The study of tribal fanaticism is one of the studies that combine the sciences of religion, history and politics in addition to sociology and economics. some of historical thinkers and researchers, especially Ibn Khaldun, have examined the study of tribal fanaticism and discussed its various concepts and the Islamic view of it